Soil and Crop Management Practices to Minimize the Impact of Waterlogging on Crop Productivity - Manik, S. M. Nuruzzaman; Pengilley, Georgina; Dean, Geoffrey; Field, Brian; Shabala, Sergey; Zhou, Meixue (Frontiers in Plant Science, 2019)
Waterlogging remains a significant constraint to cereal production across the globe in areas with high rainfall and/or poor drainage. Improving tolerance of plants to waterlogging is the most economical way of tackling the problem. However, combined agronomic, engineering and genetic solutions will be more effective. A wide range of agronomic and engineering solutions are currently being used by grain growers to reduce losses from waterlogging. In this scoping study, we reviewed the effects of waterlogging on plant growth, and advantages and disadvantages of various agronomic and engineering solutions which are used to mitigate waterlogging damage. Further research should be focused on: cost/benefit analyses of different drainage strategies; understanding the mechanisms of nitrogen loss during waterlogging and quantifying the benefits of nitrogen application; increasing soil profile de-watering through soil improvement and agronomic strategies; revealing specificity of the interaction between different management practices and environment as well as among management practices; and more importantly, combined genetic, agronomic and engineering strategies for varying environments.